Advances in heterometallic ring-opening (co)polymerisation catalysis - Weronika Gruszka (Nature Portfolio, 2021)
Improving catalyst performance for ring-opening (co)polymerisation (RO(CO)P) reactions by using heterometallic cooperativity is a promising yet underexplored strategy. Here the authors review advances in heterometallic RO(CO)P catalyst design, highlighting the overarching structure-activity trends and reactivity patterns to inform future catalyst design.